Nyeri kepala pada penyemprot vektor malaria Dengan a cypermethrin di kecamatan Kokap, kabupaten Kulon Progo Daerah istimewa yogyakarta, - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
Methods: The Untreated Controlled Group Design With Pre Test And Post Test. Results: There were 40 sprayer workers sample and 20 controls. The age of the sample and controls between 17 â 55 years old. Cephalgia were present in 14 people (35%). Spike and wave recorded by electrotroencephalogram were present in 6 people (15%). Conclusion: There should be awareness of the hazardous of fendona to make cephalgia